Pulsed pressure enhances osmotic dehydration and subsequent hot air drying kinetics and quality attributes of red beetroot. Issue 2 (23rd January 2023) - Pei, Yu-Peng; Sun, Bao-Hu; Vidyarthi, Sriram K.; Zhu, Zhi-Qiang; Yan, Sheng-Kun; Zhang, Yang; Wang, Jiqiang; Xiao, Hong-Wei
Abstract: Osmotic dehydration (OD) is one of the commonly used methods for preservation of red beetroot. However, it is a time-consuming process and microbial contamination may occur, resulting in flavor deterioration and market value reduction of products. The present study was aimed to verify whether pulsed pressure osmotic dehydration (PPOD), a newly developed non-thermal food process method can accelerate the impregnation efficiency, improve the quality of final products, and explore the mechanism involved. Results indicated that pulsed pressure of 250 kPa effectively improved the mass transfer of OD process and the following drying process. The Weibull model could describe the drying kinetics very well. The hardness of red beetroot decreased significantly ( p < 0.05) during OD process and remained stable after drying process. In addition, the PPOD and constant pressure treatments could preserve the surface color. Preserved beetroots under the pulsed pressure of 250 kPa obtained the highest score on overall acceptability, indicating it was preferred for preserved red beetroot. In conclusion, PPOD was an efficient, economical, and sustainable impregnation method for red beetroot, and these results can serve as a theoretical underpinning for analyzing the involving mechanism and exploring the excellent control parameters of impregnation process in the PPOD food processing.